Pembelajaran Kitab Mūn-Mūn Dalam Meningkatkan Pemahaman Ilmu Nahwu Dan Sharraf Bagi Santri Mubtadiin Di Pondok Pesantren Al-Muqri As-Salafi Lil Banin Prenduan Sumenep Madura - Ainul Yakin; Rahmat Fajar Al-Qusyairi JNZ; Asy'ari Asy'ari (Dirosat : Journal of Islamic Studies, 2020)
This article aims to find out the learning of the Mūn-Mūn book in increasing the understanding of Nahwu and Sharraf science for students, and to find out the results of learning the Mūn-Mūn book in increasing the understanding of Nahwu and Sharraf science for students and what are the supporting and inhibiting factors in the teaching and learning process Nahwu science at Al-Muqri As-Salafi Islamic Boarding School Lil Banin Prenduan. This research was designed using a qualitative approach with a descriptive type. Sources of data in the research consisted of primary data, namely caregivers, teachers and students. Meanwhile, secondary data is in the form of documents at the Al-Muqri As-Salafi Islamic Boarding School Lil Banin Prenduan Sumenep. Data collection techniques include interviews, observation and documentation. The data analysis technique uses a single case design with the data analysis model introduced by Miles and Hiberman, namely the data analysis process is carried out starting from the process of data collection, presentation and verification or drawing conclusions. The conclusion of the research is that learning the Mūn-Mūn book in increasing the understanding of Nahwu and Sharraf science for students includes the planning stages, in the form of an initial foundation for mubtadi students to understand which contains the Madura language. The implementation stages are in the form of an emphasis on direct practical learning methods using the yellow book. Assessment/evaluation stages are in the form of routine assessments and summative assessments at the end of the semester. The learning outcomes are that students can understand the books of Alfiah, Imriti, and the book of Naqmul Maqsud, students can understand I'rob and the position of sentences in the yellow book and Mubtadiin students can know the arrangement of Arabic sentences. While the supporting factors are enthusiasm in the teacher and students and practice them. While the inhibiting factors are elderly students due to illness or going home.